2005
DOI: 10.1681/asn.2004070593
|View full text |Cite
|
Sign up to set email alerts
|

Focal and Segmental Glomerulosclerosis

Abstract: Focal and segmental glomerulosclerosis (FSGS) is one of the most common primary glomerular diseases to terminate in ESRD.A complete remission (CR) confers an excellent long-term prognosis, but the quantitative benefits of partial remissions (PR) have not been defined. This study evaluated the rate of renal function decline (slope of creatinine clearance) and renal survival in nephrotic FSGS patients with CR, PR, or no remission. It also examined relapse rate from remission and its impact on outcome. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
212
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(235 citation statements)
references
References 27 publications
15
212
1
7
Order By: Relevance
“…Decreasing suPAR is also associated with greater odds of achieving complete remission. 18 These findings are based on analysis of proteinuria as a continuous rather than a discrete variable, as was done in the evaluation of efficacy in the FSGS CT cohort. 19 We acknowledge that our findings from the FSGS CT are exploratory in nature because suPAR was assayed in a subset of the total study cohort and patients could be withdrawn from the study if there was no evidence of response after 26 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing suPAR is also associated with greater odds of achieving complete remission. 18 These findings are based on analysis of proteinuria as a continuous rather than a discrete variable, as was done in the evaluation of efficacy in the FSGS CT cohort. 19 We acknowledge that our findings from the FSGS CT are exploratory in nature because suPAR was assayed in a subset of the total study cohort and patients could be withdrawn from the study if there was no evidence of response after 26 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, the risk reduction for the primary outcome was much greater than those in the NR group. The importance of PR has been suggested for various glomerulopathies (1,21,22). In particular, Reich et al indicated that patients with IgAN who initially presented with proteinuria .3 g/d and achieved PR (,1 g/d) had similar outcomes to patients with persistent proteinuria of ,1 g/d during follow-up and also had superior prognoses to patients who never achieved remission (1).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid sensitivity was defined as complete or partial remission in subjects who had received at least 8 wk of daily or alternate-day glucocorticoid therapy. 26 Glucocorticoid sensitivity was evaluable for 56 African Americans with FSGS (26% of the total number of cases); the other subjects did not receive the required course of glucocorticoids.…”
Section: Study Participantsmentioning
confidence: 99%